Development of Integrated Smart Apps Creator Media with Guided Inquiry Learning Model on Reaction Rate Material - Ramadhoni, Yudi; Muchtar, Zainuddin (UNDIKMA, 2024)
This research is about developing Smart Apps Creator media integrated with a guided inquiry learning model on reaction rate material. The type of research carried out is Research and Development or what is known as Research and Development (R&D). The aim of this research is to develop learning media using Smart Apps Creator which is integrated with a guided inquiry learning model on reaction rate material, as well as getting validation from experts regarding this media and knowing the responses of teachers and students to its use. The development model used in this research is the 4-D model. The stages of 4-D development are the stages of definition, design, development and dissemination. This research produces smart apps Creator learning media that is integrated with the guided inquiry learning model on reaction rate material. The results of the media expert validation assessment obtained an average of 89.6% (very valid). The results of the teacher response assessment obtained an average of 89.5% (very practical) and the results of the student response assessment obtained an average of 82.2% (very practical).